Proceedings of the 41st ACM SIGPLAN Conference on Programming Language Design and Implementation 2020
DOI: 10.1145/3385412.3385983
|View full text |Cite
|
Sign up to set email alerts
|

Type-directed scheduling of streaming accelerators

Abstract: Designing efficient, application-specialized hardware accelerators requires assessing trade-offs between a hardware module's performance and resource requirements. To facilitate hardware design space exploration, we describe Aetherling, a system for automatically compiling data-parallel programs into statically scheduled, streaming hardware circuits. Aetherling contributes a space-and time-aware intermediate language featuring data-parallel operators that represent parallel or sequential hardware modules, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Lift-hls [19], Cλash [1] and Aetherling [10] have recently shown the advantages of functional IR. Similar to Shir's vector and stream types, these two feature space-and time-aware types to express parallelism and pipelining on a high level of abstraction.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Lift-hls [19], Cλash [1] and Aetherling [10] have recently shown the advantages of functional IR. Similar to Shir's vector and stream types, these two feature space-and time-aware types to express parallelism and pipelining on a high level of abstraction.…”
Section: Related Workmentioning
confidence: 99%
“…Aetherling [10] has presented results on a larger set of applications. However, they have only demonstrated results in simulation using a simple memory model and have not discussed how memory would be handled on a real hardware.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We classify related research literature across five dimensions, as shown in Table 3. The types of parallelism supported by each piece of research vary from ILP within Basic Block boundaries [33,34], to loop level [7,10,12,18], task level parallelism [16,19] and Tensor level [15]. Early DSE, one of the most important aspects of Trireme, is in many instances not supported by tools developed to expose and exploit parallelism in HW acceleration [12,15,16,20,24].…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, Spatial [10] is an early DSE infrastructure that uses Hypermapper 2.0 [18] in order to apply early DSE, however the parts to be accelerated need to be user-defined and high level languages are not supported as input. Aetherling [7] applies early DSE as well and can be configured onto FPGAs, but it is restricted to loop level parallelism only and, like Spatial, does not support high level languages (C/C++).…”
Section: Related Workmentioning
confidence: 99%